Pascal on passions - Gomilko , Olga (Sententiae, 2000)
Author examines the problematic relationship between rationality and passions in Pascal’s doctrine in four contexts: (1) the foundations of New European metaphysics, which are characterized by the desomatization of man - the removal of corporeality from the essential human attributes; (2) the tradition of opposition to this desomatization in Modern metaphysics, as well as in the philosophy of the nineteenth and twentieth centuries. (3) the Christian doctrine of man as a fundamentally spiritual and corporeal being, as well as the doctrine of the incarnation of Jesus Christ, the passion of Christ and the atonement of original sin; (4) the Christian doctrine of love as a force that overcomes the internal contradiction of human nature. Based on the results of the study of Pascal’s doctrine of the passions, the author argues for the view of Pascal as the historically first opponent of the 1) foundation of New European metaphysics, as well as a thinker who simultaneously combined deep Christian religiosity and Modern rationality.